2015
DOI: 10.1080/21645515.2015.1106656
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase seasonal influenza vaccine coverage in healthcare workers: A systematic review and meta-regression analysis

Abstract: Influenza vaccination is recommended for healthcare workers (HCWs), but coverage is often low. We reviewed studies evaluating interventions to increase seasonal influenza vaccination coverage in HCWs, including a meta-regression analysis to quantify the effect of each component. Fourty-six eligible studies were identified. Domains conferring a high risk of bias were identified in most studies. Mandatory vaccination was the most effective intervention component (Risk Ratio of being unvaccinated [RR unvacc ] D 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 84 publications
(121 reference statements)
8
96
1
5
Order By: Relevance
“…A study conducted in the US showed that vaccination coverage among HCWs, who reported at least two interventions, was about twice than HCWs without any intervention at the workplace [29]. These results were similar to those shown by a recent review on interventions to increase influenza vaccination coverage among HCWs, which reported that vaccination uptake had a direct relation with multiple intervention strategies adopted in health care settings [30][31][32]. For all these reasons, a "multiple interventions" strategy was developed to guarantee a substantial increase in vaccination coverage rates among HCWs at the UH of Palermo.…”
Section: Discussionsupporting
confidence: 69%
“…A study conducted in the US showed that vaccination coverage among HCWs, who reported at least two interventions, was about twice than HCWs without any intervention at the workplace [29]. These results were similar to those shown by a recent review on interventions to increase influenza vaccination coverage among HCWs, which reported that vaccination uptake had a direct relation with multiple intervention strategies adopted in health care settings [30][31][32]. For all these reasons, a "multiple interventions" strategy was developed to guarantee a substantial increase in vaccination coverage rates among HCWs at the UH of Palermo.…”
Section: Discussionsupporting
confidence: 69%
“…4,5 Similarly, healthcare workers (HCW) have lingering misconceptions of vaccines and vaccine-preventable diseases and are one of the major causes for reduced uptake of recommended vaccines. 6 This lack of confidence contributes to the occurrence of vaccine hesitancy, threatening the effectiveness of vaccination programs. 7 In order to maintain vaccine-acquired herd immunity, it is essential that the vaccination coverage of the population remains above specific threshold values.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite the strong evidence of vaccine effectiveness and the easy access to influenza vaccination, the uptake rate of influenza vaccine among HCWs remains low and below recommended targets in many countries. 2,3,6,7 In Italy, influenza vaccination is strongly recommended for healthcare professionals, but a national figure about the coverage achieved among HCWs is not current available; according to several ad hoc studies, vaccine coverage among this group remains much lower than target established by the Ministry of Health. 8,9 Many studies have largely examined the reasons for rejecting or accepting influenza vaccination among HCWs and the most effective interventions for improving vaccine acceptance, some of them seem to indicate that oldest HCWs, who never got vaccinated, are quite difficult to immunize.…”
Section: Introductionmentioning
confidence: 99%